(3hQbGJ aj GdeQSdGJ dcd EfSGf heG jfGSHgs - (3eLghds
(3ChdgG (B:s
(3eQGSdI ddCTQGa aQY GdTLQI GdRcjI hNdGUI GdSdSdI GdeUWajI, hWQGR GdYUGHI GdYdhjIs
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf hdG YOhGf EdG Ydi GdXGdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs